2013
DOI: 10.1017/s0022149x13000059
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Trichinella spiralis infection and induced colitis in mice

Abstract: Inflammatory bowel disease (IBD) is a chronic relapsing inflammation afflicting any part of the bowel wall as a result of a deregulated and inappropriate immune response. In recent years, experimental and clinical evidence has demonstrated that infection with parasitic worms could protect hosts from IBD. The aims of this study were to determine if the underlying mechanism of the host immune regulation inherent to Trichinella spiralis infection involves Foxp3-expressing regulatory T cells, and to gain insight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…The histopathological score of lung tissue inflammation in T. spiralis infected groups was significantly reduced than non-infected induced asthma group. Similar reduction in the inflammatory reaction was also reported in models of arthritis and colitis treated with T. spiralis infection (Cheng et al, 2018;Ashour et al, 2014) signified a direct effect of T. spiralis infection in reduction of the inflammatory response. Also, the results of cell counts in the blood and BALF were supportive to histopathological findings as there was significant reductions in the total leukocyte counts, eosinophil counts, neutrophil counts in preventive groups compared to induced asthma group.…”
Section: Discussionsupporting
confidence: 73%
“…The histopathological score of lung tissue inflammation in T. spiralis infected groups was significantly reduced than non-infected induced asthma group. Similar reduction in the inflammatory reaction was also reported in models of arthritis and colitis treated with T. spiralis infection (Cheng et al, 2018;Ashour et al, 2014) signified a direct effect of T. spiralis infection in reduction of the inflammatory response. Also, the results of cell counts in the blood and BALF were supportive to histopathological findings as there was significant reductions in the total leukocyte counts, eosinophil counts, neutrophil counts in preventive groups compared to induced asthma group.…”
Section: Discussionsupporting
confidence: 73%
“…In line with these findings, a recent paper also showed that amelioration of acetic acid-induced ulcerative colitis in mice was more pronounced when infection by the related nematode T. spiralis preceded colitis induction (Ashour et al , 2014). This raises a question about the presence of adult worms by day 36 post-infection in earlier induction of colitis.…”
Section: Discussionmentioning
confidence: 60%
“…In recent years, there has been extensive application of experimental models based on the use of helminths to ameliorate chemically induced ulcerative colitis. Although results have been somewhat contradictory in cases where the Hymenolepis diminuta tapeworm was used (Reardon et al , 2001; Wang et al , 2010), most of the studies carried out with nematodes such as Trichinella spiralis or Heligmosomoides polygyrus clearly demonstrated beneficial effects (Khan et al , 2002; Motomura et al , 2008, Sutton et al , 2008; Ashour et al , 2014). The basis for the therapeutic ability of these helminths is supported by their proven ability to modulate the immune response towards predominance of the Th2 type through triggering T and B regulatory cells, resulting in down-regulation of Th1-type responses typically associated with this kind of inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding parasitic infection, T. spiralis were proved to stimulate the Foxp3+ T‐reg. cells in the intestine . Colonic infiltration with Foxp3+ T‐reg.…”
Section: Discussionmentioning
confidence: 99%